Enzyme reaction engineering for the conversion of emulsified di-rhamnolipid by free and immobilized Naringinase - Magario, Ivana (KIT Scientific Publishing, 2009)
Process optimization was conducted for the conversion of the aggragate-building substrate di-rhamnolipid to mono-rhamnolipid by Alpha-L-rhamnosidase from Penicillium decumbens and resulting in: (I) selection of optimal reaction conditions for enzyme activity and stability, (II) modeling of the reaction time course assuming mixed aggregates as a second phase, and (III) high mass diffusion resistances were completely overcome by the use of non-porous magnetic enzyme micro-carriers.